Microbial Community Structure in Arctic Lake Sediments Reflect Variations in Holocene Climate Conditions - Møller, Tor Einar; van der Bilt, Willem G.M.; Roerdink, Desiree L.; Jørgensen, Steffen L. (Frontiers in Microbiology, 2020)
Reconstruction of past climate variability using physical and geochemical parameters from lake sedimentary records is a well-established and widely used approach. These geological records also contain a vast and active microbial community, which are believed to be responsive to their surroundings at the time of deposition, and proceed to interact intimately with their physical and chemical environment for millennia after deposition. However, few studies have investigated the potential legacy of past climate conditions on the contemporary microbial community structure. We analysed two Holocene-length (past 10 ka BP) sediment cores from the glacier-fed Ymer Lake, located in a highly climate-sensitive region on south-eastern Greenland. By combining physical proxies, solid as well as fluid geochemical data, and microbial community profiling in a comprehensive statistical framework, we show that the microbial community structure in Ymer Lake cluster according to established lithological units, and thus capture past environmental conditions and climatic transitions. Our findings suggest that the contemporary sedimentary microbial community of Ymer Lake retains a strong linkage to climate conditions at the time of deposition - even millennia after burial. The strong coupling between physical and geochemical shifts in the lake and microbial variation highlights the potential of molecular microbiological data to strengthen and refine existing sedimentological classifications of past environmental conditions and transitions. Furthermore, this coupling implies that, within Ymer lake, microbially controlled transformation and partitioning of geochemical species today is still affected by climatic conditions that prevailed thousands of years back in time.